2019
DOI: 10.1177/0011128719839354
|View full text |Cite
|
Sign up to set email alerts
|

Out-Group Animus and Punitiveness in Latin America

Abstract: The social threat perspective anticipates that members of racial/ethnic out-groups might be perceived as socially, politically, or economically threatening; criminally inclined; and in need of social control via the criminal justice system. In light of this framework, the current study examines the influence of out-group animus on punitive sentiments in the rarely explored context of Latin America. Data from the 2012 AmericasBarometer survey collected in nine countries ( N = 15,145) are analyzed, and the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 93 publications
(165 reference statements)
1
11
0
Order By: Relevance
“…Much of this work builds on group-based threat theories, which posit that the association between subordinate groups and criminality is a powerful means of maintaining dominant group power, allowing dominant group members to justify harsh policies that primarily target minority groups by claiming they are necessary to protect the innocent (Unnever 2014). 4 A link between racial and ethnic animus and punitive attitudes has also been documented in Europe, Canada, Japan (Ousey and Unnever 2012; Unnever and Cullen 2010; Unnever, Cullen, and Jonson 2008), and Latin America (Lehmann et al 2020).…”
Section: Protester Identity and Nonviolent Resistancementioning
confidence: 94%
See 1 more Smart Citation
“…Much of this work builds on group-based threat theories, which posit that the association between subordinate groups and criminality is a powerful means of maintaining dominant group power, allowing dominant group members to justify harsh policies that primarily target minority groups by claiming they are necessary to protect the innocent (Unnever 2014). 4 A link between racial and ethnic animus and punitive attitudes has also been documented in Europe, Canada, Japan (Ousey and Unnever 2012; Unnever and Cullen 2010; Unnever, Cullen, and Jonson 2008), and Latin America (Lehmann et al 2020).…”
Section: Protester Identity and Nonviolent Resistancementioning
confidence: 94%
“…A number of studies, for example, find that anti-Muslim prejudice in Europe is significantly higher than prejudice against other foreigners or immigrants (Adida, Laitin, and Valfort 2016; Spruyt and van der Noll 2017; Strabac and Listhaug 2008). And in Latin America, studies have found evidence for negative stereotypes of Black people (Lehmann et al 2020; Peña, Sidanius, and Sawyer 2004).…”
Section: Protester Identity and Nonviolent Resistancementioning
confidence: 99%
“…The breadth and diversity of these surveys provide opportunities for exploring criminological phenomena and theory testing (Schaible, 2012). Using these datasets, researchers have examined topics related to anomie (Hovermann et al, 2016;Zhao & Cao, 2010), victimization (Bateson, 2012;Sulemana, 2015), feelings of safety (Buil-Gil et al, 2019), trust in police (Cao & Dai, 2006;Corbacho et al, 2015;Jackson et al, 2011;Singer et al, 2019), intimate partner violence (Goodson & Hayes, 2018;Heise & Kotsadam, 2015), bullying (Chester et al, 2015;Smith-Khuri et al, 2004), vigilantism and punishment (Lehmann et al, 2020;Nivette, 2016), and delinquency and youth groups (Enzmann et al, 2010;Gatti et al, 2011Gatti et al, , 2015.…”
Section: Cross-national Datamentioning
confidence: 99%
“…There is considerable empirical evidence to suggest that the minority group threat hypothesis has impacted significantly on crime-control policy in the United States (e.g., Behrens et al, 2003; Earl et al, 2003; Jacobs & Carmichael, 2001; Liska et al, 1985). However, only a few studies have focused on the importance of racial animus as a source of punitive attitudes in contexts other than the United States and Europe (Lehmann et al, 2020). The present cross-national study aims to extend the literature by applying the racial animus model to assess punitive attitudes for different crime types.…”
Section: The Racial Animus Modelmentioning
confidence: 99%